Elucidating gut microbiota–hippocampus interactions in emerging psychosis: A new perspective for the development of early interventions for memory impairments - Iseli, Galya C.; Ulrich, Sarah; Schmidt, André (Frontiers in Psychiatry, 2023)
Hippocampal dysregulation might be a key pathophysiological factor for memory impairments in psychosis. Contemporary models particularly postulate that an imbalance of hippocampal glutamate and GABA leads to impaired memory and may thus serve as a therapeutic target to improve memory deficits. However, currently available interventions in early stages of psychosis do not explicitly target hippocampal pathology. A novel approach for manipulating hippocampus-dependent memory processes is provided via the gut microbiota. In this perspective article, we first recapitulate compelling evidence for emerging hippocampus pathology during the development of psychosis. The following sections emphasize the critical role of the gut microbiota in hippocampus plasticity and memory, and summarize existing evidence about gut microbiota alterations in different stages of psychosis. Finally, we propose a novel conceptual roadmap for future studies deciphering gut microbiota – hippocampus synergisms in emerging psychosis and argue that specific microbial supplementation might be promising for improving hippocampus-dependent memory deficits in early stages of psychosis.